Demystifying the differences in the impact of training and incentives on employee performance: Mediating roles of trust and knowledge sharing - Sharma, Piyush; Lee, Yuk Ling Angie; Malik, Ashish; Rosenberger III, Philip J (Emerald, 2020)
Purpose